2019
DOI: 10.1002/essoar.10501105.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large-eddy simulation of idealized hurricanes at different sea surface temperatures

Abstract:  The hurricane structure changes as sea surface temperature increases: the distribution function of wind speed changes from single peak to bimodal.  The scale of turbulent eddies increases as sea surface temperature increases. For hurricane intensity, a horizontal grid size near 200 m is sufficient for a converged solution.  A new damage indicator is proposed for hurricane disaster risks.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Large eddy simulation by Rotunno et al (2009) suggested that an evident increase in WMS related to resolved turbulence, while sustained surface wind in terms of time averaged surface wind began to decrease with decreasing horizontal grid spacing. A possible explanation for lower sustained surface wind in finer resolution of LES is the larger mixing effects of resolved turbulence (Ren et al, 2020;Rotunno et al, 2009). In our results, the large difference in sustained surface wind in terms of the WMS on 2-km grid between the S-H and YSU, and RLES is mainly due to the fact that finer scale turbulences(<2-3 km) can be explicitly resolved in the latter than the former for the finer horizontal grid spacing.…”
Section: Tc Intensity and Structurementioning
confidence: 45%
See 2 more Smart Citations
“…Large eddy simulation by Rotunno et al (2009) suggested that an evident increase in WMS related to resolved turbulence, while sustained surface wind in terms of time averaged surface wind began to decrease with decreasing horizontal grid spacing. A possible explanation for lower sustained surface wind in finer resolution of LES is the larger mixing effects of resolved turbulence (Ren et al, 2020;Rotunno et al, 2009). In our results, the large difference in sustained surface wind in terms of the WMS on 2-km grid between the S-H and YSU, and RLES is mainly due to the fact that finer scale turbulences(<2-3 km) can be explicitly resolved in the latter than the former for the finer horizontal grid spacing.…”
Section: Tc Intensity and Structurementioning
confidence: 45%
“…The fine-scale turbulence of modeled tropical cyclones are known to be sensitive to different surface temperature. A recent study by Ren et al (2020) discusses the sensitivity of the fine-scale turbulence in an idealized tropical cyclone to different constant SST in the WRF model. However, the feedback between storm and more realistic SST and its effect on TCBL remain to be studied.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that variations in horizontal grid spacing can influence the simulation of fine‐scale features in the TCBL (Green & Zhang, 2015; Ren et al., 2020; Rotunno et al., 2009). As introduced in Section 2, three additional sensitivity simulations were carried out by decreasing the grid spacing to 166 m. The simulated fine‐scale features in this group of simulations in Figure 7 show the simulated horizontal distribution of vertical velocity (m s −1 ) at a height of 183 m with wavelengths larger than 1 km.…”
Section: Fine‐scale Turbulencementioning
confidence: 99%
“…Tropical cyclone (TC) turbulence in the planetary boundary layer (PBL) is thought to be crucial for sustained and gusty winds, which can cause severe socioeconomic impacts (Emanuel, 1995; Wurman & Kosiba, 2018). High‐resolution simulations are extremely important for reproducing fine‐scale turbulence in the PBL (Green & Zhang, 2015; Ren et al., 2020; Rotunno et al., 2009; Wu et al., 2018) and forecasting the sustained intensity of a TC (Braun & Tao, 2000; Gopalakrishnan et al., 2013; Zhang et al., 2017, 2020), as some turbulent structures cannot be fully resolved until a sub‐kilometer or finer resolution is applied.…”
Section: Introductionmentioning
confidence: 99%